2015
DOI: 10.1021/acs.jafc.5b01366
|View full text |Cite
|
Sign up to set email alerts
|

Yield, Quality, and Nutrient Concentrations of Strawberry (Fragaria ×ananassa Duch. cv. ‘Sonata’) Grown with Different Organic Fertilizer Strategies

Abstract: Four combinations of two solid organic fertilizers (Monterra Malt and chicken manure) applied before planting and two liquid organic fertilizers (broad bean and Pioner Hi-Fruit/K-Max) given through drip irrigation (fertigation) were compared with inorganic fertilization regarding growth, yield, nutrient concentration, and fruit quality of strawberries. Broad bean fertigation combined with Monterra Malt resulted in a similar fruit yield as inorganic fertilizer and a higher yield than Monterra Malt combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 36 publications
3
23
2
1
Order By: Relevance
“…The higher TSS recorded in 'Ventana' grown organically could be due to lower fruit water content (i.e. greater dry matter percentage), as observed in previous studies [34,36]. Furthermore, the higher availability of N in the conventional farming may also explain the lower TSS in berries, as in Cantliffe et al [43], and shows that increasing amounts of N will decrease strawberry fruit TSS.…”
Section: Mean Weight Firmness and Flavor Compoundssupporting
confidence: 57%
See 1 more Smart Citation
“…The higher TSS recorded in 'Ventana' grown organically could be due to lower fruit water content (i.e. greater dry matter percentage), as observed in previous studies [34,36]. Furthermore, the higher availability of N in the conventional farming may also explain the lower TSS in berries, as in Cantliffe et al [43], and shows that increasing amounts of N will decrease strawberry fruit TSS.…”
Section: Mean Weight Firmness and Flavor Compoundssupporting
confidence: 57%
“…The greater dry matter percentage may be due to a higher proportion of cell wall content in the small-sized 'Ventana' organic berries compared with the large-sized organic fruits [35,36] as a result of the lower nitrogen concentration in organic fruit [37].…”
Section: Mean Weight Firmness and Flavor Compoundsmentioning
confidence: 99%
“…High moisture in soils facilitated the release of compounds accumulated by soil microbes and motivated microbial activity and growth [30]. High EC may result in nitrogen depletion, nutrient reduction, and decrease in strawberry yield [3132]. The pH level and EC both declined after treatment for six years.…”
Section: Resultsmentioning
confidence: 99%
“…On the sixth year, strawberry yields increased by 555.91 kg/ha compared with that without applying soil conditioner (Table 3). This phenomenon was greatly associated with pH changes, because the optimum pH for strawberry growth is 5.5–6.5 [31]. Plant productivity is more sensitive to soil pH and nutrient [53], because it directly influences the uptake of mineral nutrients by the soil microorganism.…”
Section: Resultsmentioning
confidence: 99%
“…Although studies have shown that all mineral fertilizers (N, P, and K) and water have effects on the yield and quality of strawberries, most of them only focused on either the effect of water [26–28] or the effect of fertilization [29–33]. The combined application of N, P, and K (NPK) fertilizers and water for high yield and good fruit quality is rarely reported [27,31,34]. Thus, the interaction effect among N, P, and K fertilizers and water on the strawberry yield and fruit quality should be investigated.…”
Section: Introductionmentioning
confidence: 99%